Radical degradation stability of ether linkage in N, N, N′, N′-tetraoctyldiglycolamide and related organic extractants: A density functional study. (January 2017) - Koubský, Tomáš; Fojtíková, Jaroslava; Kalvoda, Ladislav
Abstract: N, N, N′, N′ -tetraoctyldiglycolamide (TODGA) has been recently subjected to extensive investigation as an organic extractant which can be used to separate trivalent actinides and lanthanides from spent nuclear fuel. In this paper, computer simulations based on Density Functional Theory (DFT) were performed in order to theoretically analyse molecular stability of TODGA and its two derivatives, methyl tetraoctyldiglycolamide (TWE-21) and dimethyl tetraoctyldiglycolamide (TWE-14). Gaussian 09 and DMol 3 computational codes were used to evaluate electronic structure- and orbital-based stability descriptors together with possible reaction pathways for a model degradation reaction. Calculated results were compared to those from prior published experimental observations with findings generally corresponding except in regards to kinetic behavior of TWE-21. Graphical abstract: Highlights: Radical degradation stability of TODGA and derivatives is simulated by DFT. Calculated bond orders indicate that the weakest location is the ether bond. Radical degradation of TODGA derivatives is predicted by Fukui function. Methylated TODGA derivative TWE-14 is predicted to be more stable than TODGA. Thermodynamic control of degradation processes is possible.